Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3x-2}{8}=\frac{5y+6}{3}=\frac{3x-5y-8}{8-3}=\frac{3x-5y-8}{5}\)
\(+,3x=5y+8\Rightarrow\frac{5y+6}{8}=\frac{5y+6}{3}\Rightarrow y=-\frac{6}{5}\Rightarrow x=\frac{2}{3}\)
\(+,3x\ne5y+8\Rightarrow5=10x\Leftrightarrow x=\frac{1}{2}\Rightarrow\frac{-1}{16}=\frac{5y+6}{3}\Rightarrow....\)
\(M=\frac{\left(\frac{3}{10}-\frac{4}{15}-\frac{7}{20}\right).\frac{5}{19}}{\left(\frac{1}{17}+\frac{1}{7}-\frac{-3}{35}\right).\frac{-4}{3}}\)
\(M=\frac{\left(\frac{1}{30}-\frac{7}{20}\right).\frac{5}{19}}{\left(\frac{24}{119}+\frac{3}{35}\right).\frac{-4}{3}}\)
\(M=\frac{\frac{-19}{60}.\frac{5}{19}}{\frac{171}{595}.\frac{-4}{3}}\)
\(M=\frac{-1}{12}:\frac{-228}{595}\)
\(M=\frac{595}{2736}\)
Ta có:
\(M=\frac{\left(\frac{3}{10}-\frac{4}{15}-\frac{7}{20}\right)\times\frac{5}{19}}{\left(\frac{1}{17}+\frac{1}{7}-\frac{-3}{35}\right)\times\frac{-4}{3}}\)
\(M=\frac{\left(\frac{1}{30}-\frac{7}{20}\right)\times\frac{5}{19}}{\left(\frac{24}{119}+\frac{3}{35}\right)\times\frac{-4}{3}}\)
\(M=\frac{\frac{-19}{60}\times\frac{5}{19}}{\frac{171}{595}\times\frac{-4}{3}}\)
\(M=\frac{-1}{12}\div\frac{-228}{595}\)
\(M=\frac{595}{2736}\)
Vậy \(M=\frac{595}{2736}\)
\(8\frac{2}{9}:\left(-\frac{7}{5}\right)-5\frac{7}{9}:\frac{7}{5}\)
\(=8\frac{2}{9}.\frac{-5}{7}-5\frac{7}{9}.\frac{5}{7}\)
\(=\left(-1.8\frac{2}{9}\right).\frac{5}{7}-5\frac{7}{9}.\frac{5}{7}\)
\(=\left(-8\frac{2}{9}\right).\frac{5}{7}-5\frac{7}{9}.\frac{5}{7}\)
\(=\frac{5}{7}.\left(-8\frac{2}{9}-5\frac{7}{9}\right)\)
\(=\frac{5}{7}.-14=-10\)
a, \(\frac{-5}{9}.\left(\frac{3}{10}-\frac{2}{5}\right)\)
\(=\frac{-5}{9}.\left(\frac{3}{10}-\frac{4}{10}\right)\)
\(=\frac{-5}{9}.\frac{-1}{10}\)
\(=\frac{5}{90}\)
\(=\frac{1}{18}\)
b,\(\frac{2}{3}+\frac{-1}{3}+\frac{7}{15}\)
\(=\frac{10}{15}-\frac{5}{15}+\frac{7}{15}\)
\(=\frac{12}{15}\)
\(=\frac{4}{5}\)
c, \(\frac{3}{8}.3\frac{1}{3}\)
\(=\frac{3}{8}.\frac{10}{3}\)
\(=\frac{10}{8}\)
\(=\frac{5}{4}\)
d, \(\frac{-3}{5}+0,8.\left(-7\frac{1}{2}\right)\)
\(=\frac{-3}{5}+\frac{4}{5}.\frac{-15}{2}\)
\(=\frac{-3}{5}+\frac{-60}{10}\)
\(=\frac{-3}{5}+\frac{-30}{5}\)
\(=\frac{-33}{5}\)
e, \(\frac{2}{5}.8\frac{1}{3}+1\frac{2}{3}.\frac{2}{5}\)
\(=\frac{2}{5}.\left(8\frac{1}{3}+1\frac{2}{3}\right)\)
\(=\frac{2}{5}.10\)
\(=4\)
f, \(\frac{3}{7}.19\frac{1}{3}-\frac{3}{7}.33\frac{1}{3}\)
\(=\frac{3}{7}.\left(19\frac{1}{3}-33\frac{1}{3}\right)\)
\(=\frac{3}{7}.-14\)
\(=-6\)
~Study well~
#KSJ
\(\frac{-1}{3}.\frac{5}{7}-\frac{1}{3}.\frac{-7}{5}\)
\(=\frac{-1}{3}.\frac{5}{7}+\frac{-1}{3}.\frac{-7}{5}\)
\(=\frac{-1}{3}.\left(\frac{5}{7}+\frac{-5}{7}\right)\)
\(=\frac{-1}{3}.0=0\)
\(x\in Z\)\(\Rightarrow x+1\ne0\Rightarrow x\ne-1\)
Gọi d=(x-4,x+1)
\(\Rightarrow\hept{\begin{cases}x-4⋮d\\x+1⋮d\end{cases}}\)
\(\Rightarrow x+1-\left(x-4\right)⋮d\)\(\Rightarrow5⋮d\)
Giả sử d=5
=> \(x=5k+4\left(k\in Z\right)\)
mà \(\frac{x-4}{x+1}\)là phân số tối giản nên d=1
=>\(x\ne5k+4\)